Enzyme‐Compatible Dynamic Nanoreactors from Electrostatically Bridged Like‐Charged Surfactants and Polyelectrolytes. Issue 30 (2nd July 2018) - Thiele, Martin J.; Davari, Mehdi D.; Hofmann, Isabell; König, Melanie; Lopez, Carlos G.; Vojcic, Ljubica; Richtering, Walter; Schwaneberg, Ulrich; Tsarkova, Larisa A.
Abstract: Reported is an unanticipated mechanism of attractive electrostatic interactions of fully neutralized polyacrylic acid (PAA) with like‐charged surfactants. Amphiphilic polymer‐surfactant complexes with high interfacial activity and a solubilization capacity exceeding that of conventional micelles are formed by bridging with Ca 2+ ions. Incorporation of a protease into such dynamic nanoreactors results in a synergistically enhanced cleaning performance because of the improved solubilization of poorly water‐soluble immobilized proteins. Competitive interfacial and intermolecular interactions on different time‐ and length‐scales have been resolved using colorimetric analysis, dynamic tensiometry, light scattering, and molecular dynamic simulations. The discovered bridging association mechanism suggests reengineering of surfactant/polymer/enzyme formulations of modern detergents and opens new opportunities in advancing labile delivery systems. Abstract : Opposites attract : Reported is an unanticipated mechanism of attractive electrostatic interactions of fully neutralized polyacrylic acid with like‐charged surfactants. Amphiphilic polymer‐surfactant complexes with high interfacial activity and solubilization capacity are formed by bridging with Ca 2+ ions. Incorporation of a protease into such dynamic nanoreactors results in an enhanced cleaning performance because of the improved solubilization of poorly water‐soluble immobilized proteins.